Analisis Regional Dampak Program Beras Sejahtera dan Bantuan Pangan Non Tunai terhadap Tingkat Ketahanan Pangan Keluarga Penerima Manfaat - Hidayat, Fatqur; Hanri, Muhammad (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
Flexibility of choice in meeting nutritional needs is one of the most important factors for food assistance beneficiaries. This study evaluates the impact of the transition of food assistance schemes in Indonesia from Rastra (in-kind transfer) to BPNT (e-voucher) on the fulfillment of KPM daily calorie intake. Calorie intake itself is a nutritional indicator that is often used to measure the quantity aspect of daily nutrient intake. Using Susenas data, impact estimation was performed using the Mahalanobis distance matching (MDM) method, Kernel algorithm implementation, complemented with exact matching and regression adjustment. The results show that the Rastra and BPNT programs can increase the percentage ratio of meeting daily calorie needs by 2.4 and 4.8 points at the national level. At the regional level, the impact of the BPNT program is much higher than the Rastra program except in Maluku, North Maluku, Papua and West Papua provinces. The difference in impact shows that food assistance schemes can be influenced by the diverse characteristics of each region (price level, accessibility, and consumption preferences of the locals).